MEDICINAL PLANTS FOR TRADICIONAL USE IN THE CORCOVADO COMMUNITY, MARAJÓ MESOREGION - Pinheiro, Eduardo Antonio Abreu; Barreiros, Rayane Pereira; Gonçalves, Benedita da Costa; Gomes, Vitória Maigda Magno; de Araújo, Carla Crislem Chaves; da Silva e Silva, Joelma Câmara; Cordeiro, Elisa Monteiro; de Paulo, Marcelo Almeida (Seven Editora, 2025)
Medicinal plants are of great importance for promoting people’s health, especially for residents of rural communities such as Corcovado, located in the municipality of Breves, Marajó Mesoregion, Pará States. The study aimed to conduct na ethnobotanical survey of medicinal plants in the research site, as well as to determine their importance the health of local residents. The research was conducted through on-site visits to properties to collect socioeconomic and ethnobotanical data, and through guided tours to conduct semi-structured interviews with 49 residents. In total, 66 species from 40 botanical families were cited in the study. The most frequently cited plants were bloodroot, cow’s foot, pariri, peppermint and quebra pedra. The leaves were the most frequently cited part for preparing teas to alleviate or cure various symptoms. The categories of circulatory system disorders and endocrine diseases presented the hightest rates according to the Informant Consensus Factor. In the Corcovado Community, it was evident that the use of medicinal plants plays a central role in health, strengthening territorial belonging and sociocultural and environmental preservation.DOI: https://doi.org/10.56238/sevened2025.036-016